2015
DOI: 10.7439/ijbar.v6i2.1678
|View full text |Cite
|
Sign up to set email alerts
|

Study of Lipid profile and Paraoxonase-1 Activity in Psoriatic patients

Abstract: Background: Psoriasis is a common recurrent disease of skin characterised by excessive cell proliferation and incomplete differentiation in lesional epidermis. Aim: The present study was aimed to determine lipid parameters and paraoxonase activity in psoriatic patients. Methods: The study included 100 subjects of age group 30-60 years, out of which 50 were patients of psoriasis (Case group) and rest 50 were normal healthy individuals of same age group (Control group). Result: Our study showed significant incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Similar findings were reported by Latha and Kumar (2014) 15 Bhatia et al, (2014) 16 and Khan et al, (2017). 17 We also found a significant elevation in the mean triglyceride levels in psoriatic patients when compared to controls (p<0.05); Ghafoor et al, (2015) 18 reported similar results although Arora et al, (2015) 19 found no significant difference in triglyceride levels among psoriatic patients when compared to controls. Our study also showed a significant reduction in mean HDL-c levels in psoriatic patients when compared to controls (p<0.05).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Similar findings were reported by Latha and Kumar (2014) 15 Bhatia et al, (2014) 16 and Khan et al, (2017). 17 We also found a significant elevation in the mean triglyceride levels in psoriatic patients when compared to controls (p<0.05); Ghafoor et al, (2015) 18 reported similar results although Arora et al, (2015) 19 found no significant difference in triglyceride levels among psoriatic patients when compared to controls. Our study also showed a significant reduction in mean HDL-c levels in psoriatic patients when compared to controls (p<0.05).…”
Section: Discussionsupporting
confidence: 62%
“…Our study also showed a significant reduction in mean HDL-c levels in psoriatic patients when compared to controls (p<0.05). This finding has been supported by Arora et al, (2015) 19 and Augstin et al, (2016) 12 , whereas Dsouza and Kuruville (2013) 20 reported no significant difference in HDL-c levels among psoriatic patients and controls. Mean LDL-c levels in psoriatic patients were found to be significantly elevated in our study when compared to controls (p<0.05).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In a study of 29 patients with juvenile idiopathic arthritis, decreased arylesterase activity levels and alterations in measures of HDL particle cholesterol transport and endothelial cell migration activities were observed . In patients with PsO, studies have yielded more mixed results, showing that PON1 activity could be either increased or decreased when compared to controls, while another study found no difference in PON1 activity in PsO patients compared to controls . Three reports on PON1 activity in patients with AS were also conflicting, with 1 study showing no difference from controls and 2 studies showing a significant decrease in PON1 activity compared to controls .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, decreasing PON1 activity has been found to be associated with increasing levels of SLE disease activity and end‐organ damage. Results from several small observational studies have been conflicting with regard to the PON1 activity levels in patients with psoriasis (PsO) and in those with ankylosing spondylitis (AS) . The present study was the first to characterize serum PON1 enzymatic activity in a psoriatic disease population and to evaluate its association with the extent of psoriatic disease activity and CVD burden.…”
mentioning
confidence: 94%